(untitled) (Research, Society and Development, 2019)
This study aimed to evaluate the acceptability and nutritional profile of school meals in a public educational institution in the city of Picos-PI. For this, a cross-sectional descriptive research was developed. Regarding the assessment of acceptability, data collection was based on the redemption of hedonic scale sheets referring to the two most commonly offered preparations, applied by nutritionists responsible for school feeding in the municipality. The quantitative analysis was made by calculating the annual menu, adopting the regulation for nutritional values defined for school meals as a parameter. The qualitative profile was evaluated according to the recommendations of the National School Education Program. None of the preparations was found to achieve satisfactory acceptability. Energy and nutritional imbalances were found, and low fruit supply, little variety of preparations and non-differentiation of menus according to different age groups. The findings of this study proved that the school’s diet is in disagreement with what is regulated, so its composition should be reviewed.